2014
DOI: 10.1111/dar.12152
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of public health interventions aimed at reducing alcohol consumption and/or increasing knowledge among pregnant women

Abstract: Issues: It is well established that alcohol can cross the placenta to the foetus and can affect both physical and psychological development of the infant; however, many women continue to drink during pregnancy. It is therefore important to determine whether interventions can be successful in reducing alcohol consumption among pregnant women. Past reviews have investigated the effectiveness of clinical interventions in reducing alcohol consumption in pregnancy; however, the aim of the current review was to focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…A recent randomized trial utilizing a telephone-based brief intervention suggests that this method may achieve similar results to the in-person intervention method of moderating prenatal drinking 78 . Some additional interventions to reduce prenatal drinking that have recently been described include screening via non-healthcare community workers 79 , counseling by midwives 80 , and multimedia and educational efforts aimed at improving awareness 81 .…”
Section: Treatment Of Substance Use In Pregnancymentioning
confidence: 99%
“…A recent randomized trial utilizing a telephone-based brief intervention suggests that this method may achieve similar results to the in-person intervention method of moderating prenatal drinking 78 . Some additional interventions to reduce prenatal drinking that have recently been described include screening via non-healthcare community workers 79 , counseling by midwives 80 , and multimedia and educational efforts aimed at improving awareness 81 .…”
Section: Treatment Of Substance Use In Pregnancymentioning
confidence: 99%
“…Brief interventions [90], particularly those that utilize motivational interviewing [91,92], can reduce perinatal alcohol use. Other recent interventions to reduce perinatal drinking have included counseling by midwives [93], screening via nonmedical community workers [94], and multimedia and educational efforts aimed to improve knowledge [95]. Additionally, recent work has highlighted the importance of social support in perinatal alcohol prevention, particularly for groups wherein social support has increased significance [96].…”
Section: Alcoholmentioning
confidence: 99%
“…A recent review (Crawford-Williams et al, 2015) examined the effects of public health interventions aimed at reducing alcohol consumption during pregnancy or increasing knowledge about the issue. The review included seven studies involving pregnant women and women of childbearing age.…”
Section: Prevention Of Alcohol Consumption During Pregnancymentioning
confidence: 99%
“…Further, two of four studies involving women of fertile age reported decreased alcohol consumption after the interventions (Hanson et al, 2012;Kaskutas & Graves, 1994). The authors of the review concluded that, due to the limited number of studies on public health interventions to reduce alcohol consumption during pregnancy, the evidence of their effectiveness is limited and more research is needed (Crawford-Williams et al, 2015).…”
Section: Prevention Of Alcohol Consumption During Pregnancymentioning
confidence: 99%